Suitability Isi UU No. 21 Tahun 2008 Tentang Perbankan Syari’ah dengan Ajaran Hukum Islam - Indah, Usna Nur; Parapat, Bagus Hamdani; Maulana, Arswendo Tiyo; Batubara, Enika Diana (Jurnal Ilmiah Wahana Pendidikan, 2023)
A bank or banking institution is a financial intermediary that is typically established with the authority to accept deposits, lend money, and issue notes known as promissory notes or banknotes. Banks can be divided into two types based on their operational activities: conventional banks and Shariah banks. An Islamic bank is a bank that operates according to Shariah principles. The implementation of Shariah principles is a key differentiator from conventional banks. In essence, Shariah principles refer to Islamic Shariah, which is mainly guided by the Quran and Hadith. The rapid development of Islamic banking promises a favorable outlook. The existence of Islamic banks in Indonesia officially began in 1992 with the enactment of Law No. 7 on Banks, but since the law did not provide a sufficient legal basis for the development of Islamic banks, the government passed a new law specifically regulating Sharia Banking, namely Law No. 21 of 2008.